Generating Evidence for Program Planning: Rapid Assessment of Avoidable Blindness in Bangladesh. (3rd May 2016) - Muhit, Mohammad; Wadud, Zakia; Islam, Johurul; Khair, Zareen; Shamanna, BR; Jung, Jenny; Khandaker, Gulam
ABSTRACT: Purpose : There is a lack of data on the prevalence and causes of blindness in Bangladesh, which is important to plan effective eye health programs and advocate support services to achieve the goals of Vision 2020. Methods : We conducted a rapid assessment of avoidable blindness (RAAB) in 8 districts of Bangladesh (January 2010 – December 2012) to establish the prevalence and causes of blindness. People aged ≥50 years were selected, and eligible participants had visual acuity (VA) measured. Ocular examinations were performed in those with VA<6/18. Additional information was collected for those who had or had not undergone cataract surgery to understand service barriers and quality of service. Results : In total, 21, 596 people were examined, of which 471 (2.2%, 95% confidence interval, CI, 2.0–2.4%) were blind. The primary cause of blindness was cataract (75.8%). The majority of blindness (86.2%) was avoidable. Cataract and refractive error were the primary causes of severe visual impairment (73.6%) and moderate visual impairment (63.6%), respectively. Cataract surgical coverage for blind persons was 69.3% (males 76.6%, females 64.3%, P<0.001). The magnitude of blindness among people aged ≥50 years was estimated to be 563, 200 people (95% CI 512, 000–614, 400), of whom 426, 342 had un-operated cataract. Conclusions : In Bangladesh, the majority of blindness (86.2%) among people aged ≥50 years was avoidable, and cataract was the most important cause of avoidable blindness. Improving cataract surgical services and refraction services would be the most important step towards the elimination of avoidable blindness in Bangladesh.